Sustainable biodiesel production from agricultural lignocellulosic waste via oleaginous microbial processes - Rawitsara Intasit; Beom Soo Kim (BMC Biotechnology)
Abstract Biodiesel, a renewable and eco-friendly liquid biofuel, plays a crucial role in reducing greenhouse gas emissions. Initially, biodiesel production relied on vegetable oils, non-edible oils, and waste oils. However, these sources face challenges, including high costs, labor and land requirements, and insufficient supply to meet demand, especially in the case of waste oils. Recent research highlights the potential of lignocellulosic substrates for biodiesel production via oleaginous microorganisms, which can accumulate lipids similar to those in vegetable oils under stress conditions. This review investigates various biodiesel feedstocks from microorganisms such as microalgae, fungi, yeast, and bacteria. It details the biodiesel production process from lignocellulosic substrates, biological pretreatment and bioconversion. Additionally, the review underscores the role in biofuel and biorefinery development and briefly discusses the integration of biofuels within a circular economy framework.